Inside an Elusive Mind Prabhakaran: The First Profile of the Worlds Most Ruthless Guerrilla Leader - M R Narayan Swamy; SWAMY (Narayan M R) (Delhi Konark Publishers Pvt Ltd, 2003)
The first profile of Prabhakaran, the world$1 (Bs most ruthless guerrilla leader. Over 60,000 have been killed in the conflict in Sri Lanka. The birth of the LTTE, the founding the suicide squads etc are described in detail. By the author of the bestselling Tigers of Lankas
Keywords: Sri Lanka; LTTE; Guerrillas; Radicals; Tamil (Indic people); Politics and government